The Analysis of Production and Income of Milkfish Cultivation in North Konawe District - Limi, Muhammad Aswar (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2020)
This study aimed to determine how much production and income earned by farmers in cultivating milkfish in North Konawe District. Research on the analysis of production and income of milkfish cultivation was carried out in Motui Sub-District, North Konawe District. The population was farmers who manage milkfish cultivation as many as 130 milkfish farming businesses so that the total sample was 56 milkfish farming businesses. The sample in this study was determined by simple random sampling. The data obtained were analyzed using the analysis of production, revenue, and income. The results of this research found that milkfish cultivation has an average production of 525kg/ha and an average income of IDR6,629,945 but has a higher RC ratio of 5.8 because farmers relied on natural food as the main source of milkfish so that production costs can be minimized. The production of milkfish farming can be increased by improving the cultivation system from traditional system to intensive system